2012
DOI: 10.1590/s0103-90162012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Height-diameter relationships of tropical Atlantic moist forest trees in southeastern Brazil

Abstract: Site-specific height-diameter models may be used to improve biomass estimates for forest inventories where only diameter at breast height (DBH) measurements are available. In this study, we fit height-diameter models for vegetation types of a tropical Atlantic forest using field measurements of height across plots along an altitudinal gradient. To fit height-diameter models, we sampled trees by DBH class and measured tree height within 13 one-hectare permanent plots established at four altitude classes. To sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 27 publications
4
33
0
9
Order By: Relevance
“…Although any function may be considered superior or inferior in a par- ticular situation, in general, we found that the ChapmanRichards, Weibull, and Näslund models proved more effective for predicting the tree height of C. fortunei than other candidate models, because they had a relatively low RMSE, RMA, and AIC, and high R 2 adj values. To a certain extent, our results are consistent with findings reported previously (Crecente-Campo et al, 2014;Jiang and Li, 2010;Rupšys, 2015;Scaranello et al, 2012). Huang et al (1992) fitted and evaluated twenty nonlinear H-D functions for major Alberta species based on a dataset consisting of 13 489 trees of 16 different species, and they found that the ChapmanRichards and Weibull functions gave the most satisfactory results.…”
Section: Discussionsupporting
confidence: 90%
“…Although any function may be considered superior or inferior in a par- ticular situation, in general, we found that the ChapmanRichards, Weibull, and Näslund models proved more effective for predicting the tree height of C. fortunei than other candidate models, because they had a relatively low RMSE, RMA, and AIC, and high R 2 adj values. To a certain extent, our results are consistent with findings reported previously (Crecente-Campo et al, 2014;Jiang and Li, 2010;Rupšys, 2015;Scaranello et al, 2012). Huang et al (1992) fitted and evaluated twenty nonlinear H-D functions for major Alberta species based on a dataset consisting of 13 489 trees of 16 different species, and they found that the ChapmanRichards and Weibull functions gave the most satisfactory results.…”
Section: Discussionsupporting
confidence: 90%
“…Embora Scaranello et al (2012) tenham verificado o incremento da biomassa viva aérea com o aumento da altitude para árvores com DAP > 30 cm, o aumento da biomassa com o aumento da altitude não foi observado para árvores com DAP > 100 cm. Sob elevadas altitudes, principalmente a partir de 1500 m acima do nível do mar (VILLELA et al, 2012), o menor crescimento de Floresta Atlântica ocorre em função da diminuição da incidência da radiação solar pela formação de nuvens espessas e densa neblina, o que ocasiona menores valores de temperatura do ar e menor disponibilidade de nitrogênio e fósforo no solo para as plantas.…”
Section: Discussionunclassified
“…Posteriormente, foi realizada a medida de altura de uma subamostra de indivíduos distribuídos em diferentes classes de diâmetro ao longo do gradiente altitudinal. Essa medida foi realizada com auxílio de trenas telescópicas (alcance de 15 m) e hipsômetro eletrônico (Laser Ranger Finder, Impulse-200LR, Laser Technology Inc., Englewood, Colorado) para indivíduos maiores do que 15 m (Scaranello et al 2012). As alturas medidas em campo a partir de instrumentos de precisão foram comparadas com as alturas estimadas visualmente.…”
Section: Mediçõesunclassified
“…Meireles et al (2010) (Alves et al 2010, Scaranello et al 2012. Todas as fitofisionomias de Floresta Ombrófila Densa apresentarem uma distribuição assimétrica do número total de indvíduos.ha -1 por classe de diâmetro, com maior proporção (47-53%) de indivíduos de menor tamanho (<10 cm), os quais foram responsáveis por apenas 7-12% da área basal total.…”
Section: Riqueza De Espéciesunclassified